CT features of systemic lupus erythematosus in patients with acute abdominal pain: emphasis on ischemic bowel disease - Byun, J Y; Ha, H K; Yu, S Y; Min, J K; Park, S H; Kim, H Y; Chun, K A; Choi, K H; Ko, B H; Shinn, K S (Radiology, 1999)
To evaluate the computed tomographic (CT) features of systemic lupus erythematosus (SLE) in patients with acute abdominal pain. Special emphasis was placed on the analysis of ischemic bowel disease. The authors retrospectively reviewed the images from 39 abdominal CT examinations performed in 33 patients with SLE and acute abdominal pain. Images were evaluated for bowel wall changes, mesenteric changes, fluid collection, retroperitoneal lymphadenopathy, peritoneal enhancement, and hepatomegaly as well as for changes in other abdominal organs. Ischemic bowel disease was diagnosed if at least three of the following signs were seen: bowel wall thickening, target sign, dilatation of intestinal segments, engorgement of mesenteric vessels, and increased attenuation of mesenteric fat. Thirty-one (79%) of the 39 examinations had CT findings diagnostic of ischemic bowel disease, including symmetric bowel wall thickening (n = 29), target sign (n = 26), and mesenteric vascular engorgement and haziness (n = 31). In 24 cases, bowel wall thickening was multifocal, with variable length, and did not appear to be confined to a single vascular territory. The most common CT finding in patients with SLE and acute abdominal pain is ischemic bowel disease. CT is useful for detecting the primary cause of gastrointestinal symptoms, planning treatment, and monitoring for infarction or perforation.